Polarizing plate with phase difference layer and image display device using the same
By providing an iodine permeation inhibiting layer composed of resin and isocyanate compound on a polarizing plate with a phase difference layer, the problems of corrosion of metal components and peeling of phase difference layer in the image display device are solved, and higher durability and reliability are achieved.
Patent Information
- Application Number
- CN202180056593.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-08-11
- Filing Date
- 2021-07-16
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2041-07-16
AI Technical Summary
When applied to an image display device, the thin polarizing plate with a phase difference layer is prone to corrosion of the metal member, and the peeling problem between the phase difference layer and the adjacent layer is difficult to solve.
At least one layer of iodine permeation inhibiting layer is provided at a predetermined position of the polarizing plate with a phase difference layer. The layer consists of a resin and an isocyanate compound. The glass transition temperature of the resin is above 85°C and the weight average molecular weight Mw is above 25,000. The isocyanate compound is selected from toluene diisocyanate, diphenylmethane diisocyanate, bendimethylene diisocyanate and their derivatives. The content ratio between the resin and isocyanate compound is 95/5 to 10/90.
By providing an iodine permeation suppression layer, corrosion of the metal member can be effectively suppressed, and peeled off between the phase difference layer and the adjacent layer can be significantly reduced, thereby improving the reliability and durability of the polarizing plate.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a polarizing plate with a phase difference layer and an image display device using the same. Background Technology
[0002] In recent years, image display devices, represented by liquid crystal displays and electroluminescent (EL) displays (such as organic EL displays and inorganic EL displays), have been rapidly gaining popularity. Polarizing plates and retardation plates are representative components used in image display devices. In practice, polarizing plates with an integrated retardation layer, where the polarizing plate and retardation plate are combined (e.g., Patent Document 1), are widely used. Recently, with the increasing demand for thinner image display devices, the demand for thinner polarizing plates with retardation layers is also increasing. To achieve thinner polarizing plates with retardation layers, efforts are being made to reduce (or omit) the protective layer of the polarizing element, which contributes significantly to the thickness, and to reduce the thickness of the retardation film. However, if thin polarizing plates with retardation layers are applied to image display devices, the metal components of the image display device (e.g., electrodes, sensors, wiring, metal layers) may corrode. This corrosion of metal components is particularly pronounced in high-temperature and high-humidity environments.
[0003] Existing technical documents
[0004] Patent documents
[0005] Patent Document 1: Japanese Patent No. 3325560 Summary of the Invention
[0006] The problem the invention aims to solve
[0007] The present invention was made to solve the above-mentioned problems, and its main objective is to provide a thin polarizing plate with a phase retardation layer that suppresses corrosion of metal components and the peeling of the phase retardation layer from the adjacent layer when applied to an image display device.
[0008] Solution for solving the problem
[0009] The polarizing plate with a phase retardation layer of the present invention comprises, from the identification side, a polarizing plate including a polarizing element, a phase retardation layer, and an adhesive layer. At least one iodine permeation inhibition layer is disposed between the polarizing element and the adhesive layer. The iodine permeation inhibition layer is a solidified or thermosetting material of a coating film of an organic solvent solution of a resin. The iodine permeation inhibition layer adjacent to the phase retardation layer comprises a resin and an isocyanate compound; the resin has a glass transition temperature of 85°C or higher and a weight-average molecular weight (Mw) of 25,000 or higher; the isocyanate compound is selected from at least one of toluene diisocyanate, diphenylmethane diisocyanate, phenylene diisocyanate, and their derivatives; the content ratio of the resin to the isocyanate compound (resin / isocyanate compound) is 95 / 5 to 10 / 90.
[0010] In one embodiment, two or more of the above-mentioned iodine permeation inhibition layers are provided.
[0011] In one embodiment, all two or more iodine permeation suppression layers are disposed adjacent to the phase difference layer. In another embodiment, one of the two or more iodine permeation suppression layers is disposed adjacent to the polarizer.
[0012] In one embodiment, the thickness of the iodine permeation inhibition layer is 0.05 μm to 10 μm.
[0013] In one embodiment, the resin constituting the iodine permeation inhibition layer comprises an epoxy resin.
[0014] In one embodiment, the resin constituting the iodine permeation inhibition layer comprises a copolymer obtained by polymerizing a monomer mixture of more than 50 parts by weight of a (meth)acrylic acid monomer and more than 0 parts by weight and less than 50 parts by weight of a monomer of formula (1).
[0015]
[0016] (In the formula, X represents a functional group containing at least one reactive group selected from the group consisting of vinyl, (meth)acryloyl, styrene, (meth)acrylamido, vinyl ether, epoxy, oxetyl, hydroxyl, amino, aldehyde, and carboxyl groups; R) 1 and R 2 Each can independently represent a hydrogen atom, an aliphatic hydrocarbon group with optional substituents, an aryl group with optional substituents, or a heterocyclic group with optional substituents, R 1 and R 2 (Optional interconnections form a loop).
[0017] In one embodiment, the phase difference layer is an orientation solidification layer of a liquid crystal compound having circular or elliptical polarization functions.
[0018] In one embodiment, the phase retardation layer is a single layer. The Re(550) of the phase retardation layer is 100nm to 190nm, and the angle between the slow axis of the phase retardation layer and the absorption axis of the aforementioned polarizer is 40° to 50°.
[0019] In another embodiment, the phase retardation layer has a stacked structure of an alignment solidification layer of a first liquid crystal compound and an alignment solidification layer of a second liquid crystal compound. The Re(550) of the alignment solidification layer of the first liquid crystal compound is 200 nm to 300 nm, and the angle between its slow axis and the absorption axis of the polarizer is 10° to 20°; the Re(550) of the alignment solidification layer of the second liquid crystal compound is 100 nm to 190 nm, and the angle between its slow axis and the absorption axis of the polarizer is 70° to 80°.
[0020] In one embodiment, the total thickness of the polarizing plate with the phase retardation layer is less than 60 μm.
[0021] According to another aspect of the present invention, an image display device is provided. This image display device includes the aforementioned polarizing plate with a phase retardation layer.
[0022] In one embodiment, the image display device is an organic electroluminescent display device or an inorganic electroluminescent display device.
[0023] The effects of the invention
[0024] According to an embodiment of the present invention, by providing at least one specific iodine penetration suppression layer at a predetermined position on a thin polarizer with a phase retardation layer, corrosion of metal components can be suppressed when the polarizer with the phase retardation layer is applied to an image display device. The iodine penetration suppression layer adjacent to the phase retardation layer comprises a resin and an isocyanate compound; the resin has a glass transition temperature of 85°C or higher and a weight-average molecular weight (Mw) of 25,000 or higher; the isocyanate compound is selected from at least one of toluene diisocyanate, diphenylmethane diisocyanate, phenylene diisocyanate, and their derivatives; the content ratio of resin to isocyanate compound (resin / isocyanate compound) is 95 / 5 to 10 / 90. By providing this iodine penetration suppression layer adjacent to the phase retardation layer, peeling between the phase retardation layer and the adjacent layer (which is essentially the iodine penetration suppression layer) can be significantly suppressed in addition to the above-mentioned effects. Attached Figure Description
[0025] Figure 1A This is a cross-sectional schematic diagram of a polarizing plate with a phase difference layer according to one embodiment of the present invention.
[0026] Figure 1BThis is a cross-sectional schematic diagram of a polarizing plate with a phase difference layer according to another embodiment of the present invention.
[0027] Figure 1C This is a cross-sectional schematic diagram of a polarizing plate with a phase difference layer, which is another embodiment of the present invention.
[0028] Figure 1D This is a cross-sectional schematic diagram of a polarizing plate with a phase difference layer, which is another embodiment of the present invention.
[0029] Figure 2A This is a cross-sectional schematic diagram of a polarizing plate with a phase difference layer, which is another embodiment of the present invention.
[0030] Figure 2B This is a cross-sectional schematic diagram of a polarizing plate with a phase difference layer, which is another embodiment of the present invention.
[0031] Figure 2C This is a cross-sectional schematic diagram of a polarizing plate with a phase difference layer, which is another embodiment of the present invention.
[0032] Figure 2D This is a cross-sectional schematic diagram of a polarizing plate with a phase difference layer, which is another embodiment of the present invention.
[0033] Figure 2E This is a cross-sectional schematic diagram of a polarizing plate with a phase difference layer, which is another embodiment of the present invention.
[0034] Figure 2F This is a cross-sectional schematic diagram of a polarizing plate with a phase difference layer, which is another embodiment of the present invention. Detailed Implementation
[0035] The embodiments of the present invention will be described below, but the present invention is not limited to these embodiments.
[0036] (Definitions of terms and symbols)
[0037] The terms and symbols used in this instruction manual are defined as follows.
[0038] (1) Refractive index (nx, ny, nz)
[0039] “nx” is the refractive index in the direction where the refractive index reaches its maximum in the plane (i.e., the slow axis direction), “ny” is the refractive index in the direction orthogonal to the slow axis in the plane (i.e., the fast axis direction), and “nz” is the refractive index in the thickness direction.
[0040] (2) In-plane phase difference (Re)
[0041] “Re(λ)” is the in-plane phase difference measured at 23℃ using light with a wavelength of λnm. For example, “Re(550)” is the in-plane phase difference measured at 23℃ using light with a wavelength of 550nm. Re(λ) is calculated using the formula: Re(λ)=(nx-ny)×d when the thickness of the layer (thin film) is d (nm).
[0042] (3) Phase difference (Rth) in the thickness direction
[0043] “Rth(λ)” is the phase difference in the thickness direction measured at 23℃ using light with a wavelength of λnm. For example, “Rth(550)” is the phase difference in the thickness direction measured at 23℃ using light with a wavelength of 550nm. Rth(λ) is calculated using the formula: Rth(λ)=(nx-nz)×d when the thickness of the layer (thin film) is d (nm).
[0044] (4) Nz coefficient
[0045] The Nz coefficient is obtained by Nz = Rth / Re.
[0046] (5) Angle
[0047] When referring to angles in this specification, the angle includes both clockwise and counterclockwise directions relative to a reference direction. Therefore, for example, "45°" means ±45°.
[0048] A. Overall structure of a polarizing plate with a phase retardation layer
[0049] Figure 1A This is a cross-sectional schematic diagram of a polarizing plate with a phase retardation layer according to one embodiment of the present invention. The polarizing plate 100 with a phase retardation layer shown in the figure has, from the identification side, a polarizing plate 10, a phase retardation layer 20, and an adhesive layer 30. The polarizing plate 10 typically includes a polarizing element 11 and a protective layer 12 disposed on the identification side of the polarizing element 11. Depending on the purpose, other protective layers (not shown) may be provided on the side of the polarizing element 11 opposite to the identification side (protective layer 12). The phase retardation layer 20 is typically an alignment solidification layer of a liquid crystal compound having circular or elliptical polarization function (hereinafter sometimes simply referred to as a liquid crystal alignment solidification layer). The adhesive layer 30 is provided as the outermost layer, and the polarizing plate with the phase retardation layer can be adhered to an image display device (essentially an image display unit).
[0050] In embodiments of the present invention, at least one iodine permeation suppression layer 40 is provided between the polarizer 11 and the adhesive layer 30. The iodine permeation suppression layer is a solidified coating of an organic solvent solution of resin or a thermosetting resin. The resin is typically characterized by a glass transition temperature of 85°C or higher and a weight-average molecular weight (Mw) of 25,000 or higher. By providing this iodine permeation suppression layer at a predetermined position on the polarizer with a phase retardation layer, the movement of iodine from the polarizer to the image display device (essentially the image display unit) can be significantly suppressed when the polarizer with the phase retardation layer is applied to an image display device. As a result, corrosion of the metal components (e.g., electrodes, sensors, wiring, metal layers) of the image display device can be significantly suppressed (hereinafter, this effect is sometimes referred to as a metal corrosion suppression effect). This metal corrosion suppression effect is a characteristic of thin polarizers with phase retardation layers (typically, polarizers with phase retardation layers where the phase retardation layer is a liquid crystal alignment solidification layer). Specifically, the inventors have discovered a new problem: when a thin polarizing plate with a phase retardation layer is applied to an image display device, the metal components of the image display device sometimes corrode. Based on the presence of iodine in the corroded areas, it was determined that this corrosion of the metal components is caused by iodine. Through repeated trial and error, it was found that an iodine penetration inhibition layer (a solidified layer or thermosetting layer of a coating film of an organic solvent solution of a resin having specific Tg and Mw) is useful as a means to prevent iodine from migrating into the image display device (essentially an image display unit). Furthermore, as described later, the iodine penetration inhibition layer can be formed very thin, and by providing the iodine penetration inhibition layer, a protective layer on the opposite side to the identification side can be omitted. Therefore, through these synergistic effects, it also contributes to further thinning of the polarizing plate with the phase retardation layer.
[0051] The iodine osmosis inhibition layer 40 can be a single layer or two or more layers (e.g., two, three, or four layers). The iodine osmosis inhibition layer 40... Figure 1A In the embodiment shown, only one layer is provided between the polarizer 11 and the phase retardation layer 20. The iodine permeation inhibition layer 40 can be as follows: Figure 1B The polarizing plate 101 with a phase retardation layer shown is configured such that only one layer is provided between the phase retardation layer 20 and the adhesive layer 30; alternatively, it can be configured as follows: Figure 1C The polarizing plate 102 with phase retardation layer shown has two layers disposed between the polarizing element 11 and the phase retardation layer 20, and between the phase retardation layer 20 and the adhesive layer 30; it can also be as follows: Figure 1DThe polarizing plate 103 with a phase retardation layer shown has three layers: two layers between the polarizing element 11 and the phase retardation layer 20, and one layer between the phase retardation layer 20 and the adhesive layer 30. When the iodine penetration suppression layer is placed between the polarizing element and the phase retardation layer (especially when the polarizing element and the iodine penetration suppression layer are adjacent), it has the following advantages: it can suppress the movement of iodine from the polarizing element under high temperature and high humidity conditions, thus improving reliability. When the iodine penetration suppression layer is placed between the phase retardation layer and the adhesive layer (especially when the adhesive layer and the iodine penetration suppression layer are adjacent), it has the following advantages: it can also simultaneously prevent components other than iodine that are considered to affect metal corrosion (such as residual monomer components in the UV-cured adhesive and decomposition products of the photoinitiator) from moving into the adhesive, further improving the metal corrosion suppression effect. By providing two or more iodine penetration suppression layers, the metal corrosion suppression effect can be significantly improved. The more iodine penetration suppression layers there are, the better the metal corrosion suppression effect. The number of iodine penetration suppression layers can be determined by considering factors such as cost, manufacturing efficiency, and the total thickness of the polarizing plate with the phase retardation layer.
[0052] In an embodiment of the present invention, the iodine penetration suppression layer adjacent to the phase retardation layer in the polarizer with the phase retardation layer comprises a resin and an isocyanate compound; the resin has a glass transition temperature of 85°C or higher and a weight-average molecular weight (Mw) of 25,000 or higher; the isocyanate compound is toluene diisocyanate, diphenylmethane diisocyanate, phenylene diisocyanate, and / or their derivatives (e.g., modifiers, adducts); the content ratio of the resin to the isocyanate compound (resin / isocyanate compound) is 95 / 5 to 10 / 90. By configuring the iodine penetration suppression layer adjacent to the phase retardation layer in this way, the excellent effect of maintaining the aforementioned metal corrosion suppression effect can be maintained while significantly suppressing the peeling of the iodine penetration suppression layer from the phase retardation layer. That is, as described above, by providing an iodine penetration inhibition layer, which is a solidified or thermosetting material of an organic solvent solution of a specific resin, a very excellent metal corrosion inhibition effect can be achieved. However, it has been found that when this iodine penetration inhibition layer is disposed adjacent to a phase reversal layer (liquid crystal alignment solidification layer), the iodine penetration inhibition layer and the phase reversal layer (liquid crystal alignment solidification layer) sometimes peel off in a high humidity environment. The inventors conducted in-depth research on this peeling and found that by adding a specific isocyanate compound in a specific amount to the resin constituting the iodine penetration inhibition layer, this peeling can be significantly suppressed, thus completing the present invention. In other words, this effect solves a new problem that was previously unknown and is an unexpectedly excellent effect.
[0053] As described above, the retardation layer 20 is a liquid crystal alignment solidification layer. The retardation layer 20 can be as follows: Figures 1A to 1D The single layer shown can also have, for example, the following: Figures 2A to 2FThe stacked structure of the first liquid crystal alignment solidification layer 21 and the second liquid crystal alignment solidification layer 22 is shown. When the phase retardation layer 20 has a stacked structure, the iodine permeation suppression layer 40 can be as follows: Figure 2A The polarizing plate 104 with a phase retardation layer shown is configured such that only one layer is provided between the polarizing element 11 and the first liquid crystal alignment solidification layer 21; alternatively, only one layer (not shown) may be provided between the second liquid crystal alignment solidification layer 22 and the adhesive layer 30; alternatively, only one layer (not shown) may be provided between the first liquid crystal alignment solidification layer 21 and the second liquid crystal alignment solidification layer 22; alternatively, as shown... Figure 2B The polarizing plate 105 with phase retardation layer shown has two layers disposed between the polarizing element 11 and the first liquid crystal alignment solidification layer 21, and between the second liquid crystal alignment solidification layer 22 and the adhesive layer 30; it can also be as follows: Figure 2C The polarizing plate 106 with a phase retardation layer shown has two layers disposed between the polarizing element 11 and the first liquid crystal alignment solidification layer 21, and between the first liquid crystal alignment solidification layer 21 and the second liquid crystal alignment solidification layer 22; it can also be as follows: Figure 2D The polarizing plate 107 with a phase retardation layer shown has two layers disposed between the first liquid crystal alignment solidification layer 21 and the second liquid crystal alignment solidification layer 22, and between the second liquid crystal alignment solidification layer 22 and the adhesive layer 30; it can also be as follows: Figure 2E The polarizing plate 108 with a phase retardation layer shown has three layers disposed between the polarizing element 11 and the first liquid crystal alignment solidification layer 21, between the first liquid crystal alignment solidification layer 21 and the second liquid crystal alignment solidification layer 22, and between the second liquid crystal alignment solidification layer 22 and the adhesive layer 30; it can also be as follows Figure 2F The polarizing plate 109 with phase retardation layer shown has four layers: two layers between the polarizing element 11 and the first liquid crystal alignment solidification layer 21, one layer between the first liquid crystal alignment solidification layer 21 and the second liquid crystal alignment solidification layer 22, and one layer between the second liquid crystal alignment solidification layer 22 and the adhesive layer 30.
[0054] Figures 1A to 1D and Figures 2A to 2F As an example, the iodine permeation inhibition layer 40 can be provided at any appropriate position and in any appropriate number between the polarizer 11 and the adhesive layer 30, depending on the purpose. For example, the above embodiments can be appropriately combined, and obvious changes to the constituent elements in the above embodiments can be made. Furthermore, for example, five or more iodine permeation inhibition layers can be provided.
[0055] In a polarizing plate with a phase retardation layer, other phase retardation layers and / or conductive layers or isotropic substrates with conductive layers (not shown) may be further provided. A representative example of other phase retardation layers is that they are disposed between phase retardation layer 20 and adhesive layer 30 (i.e., outside of phase retardation layer 20). A representative example of other phase retardation layers is that their refractive index characteristics show a relationship of nz > nx = ny. A representative example of conductive layers or isotropic substrates with conductive layers is that they are disposed between iodine permeation suppression layer 40 and adhesive layer 30 (i.e., outside of iodine permeation suppression layer 40). A representative example of other phase retardation layers and conductive layers or isotropic substrates with conductive layers is that they are disposed sequentially from the phase retardation layer 20 side in the order described above. Other phase retardation layers and conductive layers or isotropic substrates with conductive layers are arbitrary layers provided as needed, and one or both may be omitted. In the case of providing conductive layers or isotropic substrates with conductive layers, the polarizing plate with a phase retardation layer can be applied to a so-called internal touchscreen type input display device in which a touch sensor is installed between the image display unit (e.g., an organic EL unit) and the polarizing plate. In an embodiment of the present invention, by disposing a conductive layer or an isotropic substrate with a conductive layer on the outside of the iodine penetration inhibition layer 40, corrosion of the conductive layer can be significantly suppressed.
[0056] A polarizing plate with a phase retardation layer can further include other phase retardation layers. The optical properties (e.g., refractive index, in-plane phase retardation, Nz coefficient, photoelastic coefficient), thickness, and placement of these other phase retardation layers can be appropriately set according to the purpose.
[0057] In practice, it is preferable to temporarily adhere a release film to the surface of the adhesive layer 30 until the polarizing plate with the phase retardation layer is ready for use. By temporarily adhering the release film, the polarizing plate with the phase retardation layer can be rolled up while protecting the adhesive layer.
[0058] The total thickness of the polarizing plate with the retardation layer is preferably 60 μm or less, more preferably 55 μm or less, even more preferably 50 μm or less, and particularly preferably 40 μm or less. The lower limit of the total thickness can be, for example, 28 μm. According to embodiments of the present invention, such an extremely thin polarizing plate with a retardation layer can be realized, and even when such an extremely thin polarizing plate with a retardation layer is applied to an image display device, corrosion of the metal components (e.g., electrodes, sensors, wiring, metal layers) of the image display device can be significantly suppressed. Furthermore, according to embodiments of the present invention, the peeling of the retardation layer from the adjacent layer (essentially an iodine penetration suppression layer) in such an extremely thin polarizing plate with a retardation layer is significantly suppressed. In addition, such a polarizing plate with a retardation layer can have extremely excellent flexibility and bending durability. Therefore, such a polarizing plate with a retardation layer can be particularly suitable for use in curved image display devices and / or bendable or foldable image display devices. It should be noted that the total thickness of the polarizing plate with the phase retardation layer refers to the sum of the thickness of the polarizing plate, the phase retardation layer (or the phase retardation layer and other phase retardation layers if other phase retardation layers are present), the iodine penetration inhibition layer, and the adhesive layer or bonding agent layer used to laminate them (i.e., the total thickness of the polarizing plate with the phase retardation layer does not include the thickness of the conductive layer or the isotropic substrate with the conductive layer and the release film that can be temporarily bonded to the adhesive layer 30 and its surface).
[0059] The polarizing plate with the phasing layer can be a single sheet or a strip. In this specification, "strip" refers to an elongated shape with a length that is sufficiently long relative to its width, such as an elongated shape with a length that is 10 times or more, preferably 20 times or more, than its width. The strip-shaped polarizing plate with the phasing layer can be rolled into a roll.
[0060] The following describes in more detail the constituent elements of the polarizing plate with a phase retardation layer. It should be noted that the adhesive layer 30 can be constructed using methods known in the art; therefore, a detailed description of the adhesive layer's structure is omitted.
[0061] B.Polarizing plate
[0062] B-1. Polarizing element
[0063] The polarizing element is typically composed of a polyvinyl alcohol (PVA) resin film containing dichroic substances. The thickness of the polarizing element is preferably 1 μm to 8 μm, more preferably 1 μm to 7 μm, and even more preferably 2 μm to 5 μm. If the thickness of the polarizing element is within this range, it can significantly contribute to the thinning of the polarizing plate with the retardation layer. Furthermore, the effects of the present invention are significant in thin polarizing plates with retardation layers using such polarizing elements.
[0064] The boric acid content of the polarizing element is preferably 10% by weight or more, more preferably 13% to 25% by weight. If the boric acid content of the polarizing element is within this range, the ease of curl adjustment during bonding can be well maintained through the synergistic effect with the iodine content described later, and curling during heating can be well suppressed, while appearance durability during heating is improved. The boric acid content can be calculated, for example, using the following formula based on the neutralization method as the amount of boric acid contained per unit weight of the polarizing element.
[0065]
[0066] The iodine content of the polarizing element is preferably 2% by weight or more, more preferably 2% to 10% by weight. If the iodine content of the polarizing element is within this range, the ease of curl adjustment during bonding can be well maintained through the synergistic effect with the aforementioned boric acid content, and curling during heating can be well suppressed, while appearance durability during heating is improved. In this specification, "iodine content" refers to the total amount of iodine contained in the polarizing element (PVA-type resin film). More specifically, iodine in the polarizing element is expressed as iodide ions (I- ions). - ), iodine molecules (I2), polyiodide ions (I3) - I5 - Iodine ions exist in various forms, and the iodine content mentioned in this specification refers to the amount of iodine containing all of these forms. Iodine content can be calculated, for example, using a standard curve method based on fluorescence X-ray analysis. It should be noted that polyiodide ions exist in polarizing elements as PVA-iodine complexes. By forming such complexes, dichroism can be exhibited in the visible light wavelength range. Specifically, the complex of PVA and triiodide ions (PVA·I₃) - It has an absorption peak near 470 nm, and the complex of PVA and pentaiodide ions (PVA·I5) - The polyiodide ion exhibits an absorption peak around 600 nm. As a result, depending on its morphology, the polyiodide ion can absorb light across a broad range of visible light. On the other hand, the iodide ion (I-) has an absorption peak around 230 nm and essentially does not participate in the absorption of visible light. Therefore, the polyiodide ion, existing as a complex with PVA, primarily participates in the absorption performance of the polarizer.
[0067] The polarizer preferably exhibits absorption dichroism at any wavelength from 380 nm to 780 nm. The single-unit transmittance Ts of the polarizer is preferably 40% to 48%, more preferably 41% to 46%. The polarization degree P of the polarizer is preferably 97.0% or more, more preferably 99.0% or more, and even more preferably 99.9% or more. The aforementioned single-unit transmittance is representative of the Y value measured using a UV-Vis spectrophotometer and corrected for visual sensitivity. The aforementioned polarization degree is representative of the parallel transmittance Tp and orthogonal transmittance Tc measured using a UV-Vis spectrophotometer and corrected for visual sensitivity, calculated using the following formula.
[0068] Polarization (%) = {(T vs. Tc) / (Tp + Tc)} 1 / 2 ×100
[0069] Polarizing elements are typically manufactured using laminates with two or more layers. Specific examples of polarizing elements obtained using laminates include those made from a resin substrate and a PVA-type resin layer coated on the resin substrate. A polarizing element obtained from a laminate of a resin substrate and a PVA-type resin layer coated on the resin substrate can be manufactured, for example, as follows: a PVA-type resin solution is coated onto a resin substrate and dried to form a PVA-type resin layer on the resin substrate, resulting in a laminate of the resin substrate and the PVA-type resin layer; the laminate is then stretched and dyed to form a polarizing element from the PVA-type resin layer. Stretching typically includes immersing the laminate in an aqueous boric acid solution. Furthermore, stretching can be further included, as needed, air stretching of the laminate at a high temperature (e.g., above 95°C) before stretching in the aqueous boric acid solution. The resulting resin substrate / polarizer laminate can be used directly (i.e., the resin substrate can be used as a protective layer for the polarizer), or the resin substrate can be peeled off from the resin substrate / polarizer laminate and any suitable protective layer for the purpose can be laminated on the peeled surface. Details of this method for manufacturing polarizers are described, for example, in Japanese Patent Application Publication No. 2012-73580 and Japanese Patent No. 6470455. The entire contents of these publications are incorporated herein by reference.
[0070] A representative method for manufacturing polarizing elements includes sequentially performing the following steps: forming a laminate by forming a polyvinyl alcohol (PVA) resin layer containing halides and polyvinyl alcohol resin on one side of a strip-shaped thermoplastic resin substrate; and subjecting the laminate to air-assisted stretching, dyeing, underwater stretching, and drying shrinkage treatment by heating while conveying it along its length to shrink it by more than 2% along its width. This provides a very thin polarizing element with excellent optical properties and suppressed unevenness in optical properties. Specifically, by introducing assisted stretching, even when PVA is coated on a thermoplastic resin, the crystallinity of PVA can be improved, achieving high optical properties. Furthermore, by simultaneously improving the orientation of PVA beforehand, problems such as decreased orientation and dissolution of PVA can be prevented when immersed in water during subsequent dyeing and stretching processes, achieving high optical properties. Moreover, when the PVA resin layer is immersed in a liquid, compared to when the PVA resin layer does not contain halides, orientation disorder and decreased orientation of polyvinyl alcohol molecules can be suppressed. This improves the optical properties of polarizing elements obtained through processes such as dyeing and underwater stretching, which involve immersing the laminate in liquid. Furthermore, by using a drying shrinkage process to shrink the laminate along its width, optical properties can be further improved.
[0071] B-2. Protective layer
[0072] The protective layer 12 is formed of any suitable thin film that can be used as a protective layer for a polarizing element. Specific examples of materials constituting the main component of this thin film include: cellulose resins such as triacetyl cellulose (TAC); transparent resins such as polyesters, polyvinyl alcohols, polycarbonates, polyamides, polyimides, polyethersulfones, polysulfones, polystyrene, polynorbornene, polyolefins, (meth)acrylic acids, and acetates. Furthermore, thermosetting or UV-curing resins such as (meth)acrylic acids, urethanes, (meth)acrylate urethanes, epoxy resins, and silicone resins can also be used. In addition, glassy polymers such as siloxane polymers can also be used. Furthermore, polymer films described in Japanese Patent Application Publication No. 2001-343529 (WO01 / 37007) can also be used. As a material for the film, a resin composition containing a thermoplastic resin having substituted or unsubstituted imide groups in the side chains and a thermoplastic resin having substituted or unsubstituted phenyl and nitrile groups in the side chains can be used, for example: resin compositions having alternating copolymers formed from isobutylene and N-methylmaleimide and acrylonitrile-styrene copolymers. The polymer film can be, for example, an extruded product of the above resin composition.
[0073] As described below, the polarizing plate with a phase retardation layer is typically disposed on the recognition side of an image display device, and the protective layer 12 is typically disposed on its recognition side. Therefore, the protective layer 12 can be subjected to surface treatments such as hard coating, anti-reflective treatment, anti-adhesion treatment, and anti-glare treatment, as needed. Furthermore / or, the protective layer 12 can be subjected to treatments that improve visual recognition when viewed through polarized sunglasses (typically, imparting (elliptical) polarization or ultra-high phase retardation). By implementing such treatments, excellent visual recognition can be achieved even when viewing the display image through polarized lenses such as polarized sunglasses. Therefore, the polarizing plate with a phase retardation layer can also be suitably applied to image display devices that can be used outdoors.
[0074] The thickness of the protective layer is preferably 10 μm to 50 μm, more preferably 10 μm to 30 μm. It should be noted that, when a surface treatment is performed, the thickness of the outer protective layer includes the thickness of the surface treatment layer.
[0075] C. Phase difference layer
[0076] As described above, the retardation layer 20 is typically a liquid crystal alignment solidification layer. By using a liquid crystal compound, the difference between nx and ny in the resulting retardation layer can be made significantly greater than that of a non-liquid crystal material, thus significantly reducing the thickness of the retardation layer used to obtain the desired in-plane retardation. As a result, further thinning of the polarizer with the retardation layer is possible. In this specification, "liquid crystal alignment solidification layer" refers to a layer in which a liquid crystal compound is aligned in a predetermined direction and this alignment state is fixed. It should be noted that "alignment solidification layer" encompasses the concept of an alignment-cured layer obtained by curing liquid crystal monomers as described later. In this embodiment, typically, rod-shaped liquid crystal compounds are aligned in a state along the slow axis direction of the retardation layer (homogeneous orientation).
[0077] Examples of liquid crystal compounds include those whose liquid crystal phase is a nematic phase (nematic liquid crystals). Liquid crystal polymers and liquid crystal monomers can be used as such liquid crystal compounds. The mechanism by which the liquid crystallization property of a liquid crystal compound is expressed can be lyotropic or thermotropic. Liquid crystal polymers and liquid crystal monomers can be used individually or in combination.
[0078] When the liquid crystal compound is a liquid crystal monomer, the liquid crystal monomer is preferably a polymerizable monomer or a crosslinking monomer. This is because the orientation state of the liquid crystal monomer can be fixed by polymerizing or crosslinking (i.e., curing). After aligning the liquid crystal monomer, the orientation state can be fixed simply by polymerizing or crosslinking the liquid crystal monomers. Here, polymers are formed through polymerization and three-dimensional network structures are formed through crosslinking, but these are non-liquid crystals. Therefore, the resulting retardation layer does not undergo the temperature-induced phase shift to liquid crystal phase, glass phase, or crystalline phase characteristic of liquid crystal compounds. As a result, the retardation layer becomes a retardation layer with extremely excellent stability, unaffected by temperature changes.
[0079] The temperature range in which liquid crystal monomers exhibit liquid crystal properties varies depending on the type. Specifically, this temperature range is preferably 40°C to 120°C, more preferably 50°C to 100°C, and most preferably 60°C to 90°C.
[0080] As the aforementioned liquid crystal monomer, any suitable liquid crystal monomer can be used. For example, polymerizable mesocrystalline compounds described in Japanese Patent Application Publication No. 2002-533742 (WO00 / 37585), EP358208 (US5211877), EP66137 (US4388453), WO93 / 22397, EP0261712, DE19504224, DE4408171, and GB2280445 can be used. Specific examples of such polymerizable mesocrystalline compounds include BASF's trade name LC242, Merck's trade name E7, and Wacker Chemie's trade name LC-Sillicon-CC3767. Nematic liquid crystal monomers are preferred, for example.
[0081] The liquid crystal alignment solidification layer can be formed as follows: an alignment treatment is performed on the surface of a specified substrate, a coating liquid containing a liquid crystal compound is coated on the surface and the liquid crystal compound is aligned along a direction corresponding to the alignment treatment, and the alignment state is fixed, thereby forming the layer. In one embodiment, the substrate is any suitable resin film, and the liquid crystal alignment solidification layer formed on the substrate can be transferred to the surface of an adjacent layer (e.g., a polarizer, an iodine penetration suppression layer).
[0082] As the above-mentioned alignment treatment, any appropriate alignment treatment can be adopted. Specifically, mechanical alignment treatment, physical alignment treatment, and chemical alignment treatment can be cited. As specific examples of mechanical alignment treatment, friction treatment and stretching treatment can be cited. As specific examples of physical alignment treatment, magnetic field alignment treatment and electric field alignment treatment can be cited. As specific examples of chemical alignment treatment, oblique vapor deposition method and photo-alignment treatment can be cited. The treatment conditions of various alignment treatments can adopt any appropriate conditions according to the purpose.
[0083] The alignment of the liquid crystal compound is carried out by treating at a temperature at which the liquid crystal phase is exhibited according to the type of the liquid crystal compound. By performing such temperature treatment, the liquid crystal compound is in a liquid crystal state, and the liquid crystal compound is aligned according to the alignment treatment direction of the substrate surface.
[0084] Regarding the fixation of the alignment state, in one embodiment, it is carried out by cooling the liquid crystal compound aligned as described above. In the case where the liquid crystal compound is a polymeric monomer or a crosslinkable monomer, the fixation of the alignment state is carried out by performing a polymerization treatment or a crosslinking treatment on the liquid crystal compound aligned as described above.
[0085] Specific examples of the liquid crystal compound and details of the method for forming the alignment solidification layer are described in Japanese Patent Application Laid-Open No. 2006-163343. The content of this publication is incorporated herein by reference.
[0086] In one embodiment, the retardation layer 20 is as Figures 1A to 1D shown as a single layer. When the retardation layer 20 is composed of a single layer, its thickness is preferably 0.5 μm to 7 μm, more preferably 1 μm to 5 μm. By using a liquid crystal compound, an in-plane retardation equivalent to that of a resin film can be achieved with a thickness significantly thinner than that of the resin film.
[0087] As described above, the retardation layer typically has a circular polarization function or an elliptical polarization function. Typically, the refractive index characteristics of the retardation layer show a relationship of nx > ny = nz. Typically, the retardation layer is provided to impart antireflection characteristics to the polarizing plate, and can function as a λ / 4 plate when the retardation layer is a single layer. In this case, the in-plane retardation Re(550) of the retardation layer is preferably 100 nm to 190 nm, more preferably 110 nm to 170 nm, and further preferably 130 nm to 160 nm. It should be noted that here, "ny = nz" includes not only the case where ny and nz are exactly equal, but also the case where they are substantially equal. Therefore, within the range not impairing the effects of the present invention, there may be cases where ny > nz or ny < nz.
[0088] The Nz coefficient of the phase retardation layer is preferably 0.9 to 1.5, more preferably 0.9 to 1.3. By satisfying this relationship, when the resulting polarizing plate with the phase retardation layer is used in an image display device, very excellent reflective hue can be achieved.
[0089] The retardation layer can exhibit anomalous dispersion wavelength characteristics, where the phase difference increases with the wavelength of the measurement light; normal dispersion wavelength characteristics, where the phase difference decreases with the wavelength of the measurement light; or flat wavelength dispersion characteristics, where the phase difference hardly changes with the wavelength of the measurement light. In one embodiment, the retardation layer exhibits anomalous dispersion wavelength characteristics. In this case, the Re(450) / Re(550) ratio of the retardation layer is preferably 0.8 or more and less than 1, more preferably 0.8 or more and less than 0.95. With this configuration, very excellent anti-reflection properties can be achieved.
[0090] The angle θ between the slow axis of the retardation layer 20 and the absorption axis of the polarizer 11 is preferably 40° to 50°, more preferably 42° to 48°, and even more preferably about 45°. If the angle θ is in this range, by fabricating the retardation layer into a λ / 4 plate as described above, a polarizing plate with a retardation layer that has very excellent circular polarization characteristics (resulting in very excellent anti-reflection characteristics) can be obtained.
[0091] In another embodiment, the phase difference layer 20 can be as follows: Figures 2A to 2FThe diagram shows a stacked structure having a first liquid crystal alignment solidification layer 21 and a second liquid crystal alignment solidification layer 22. In this case, either the first liquid crystal alignment solidification layer 21 or the second liquid crystal alignment solidification layer 22 can function as a λ / 4 plate, and the other as a λ / 2 plate. Therefore, the thicknesses of the first liquid crystal alignment solidification layer 21 and the second liquid crystal alignment solidification layer 22 can be adjusted to obtain a desired in-plane phase difference between the λ / 4 plate and the λ / 2 plate. For example, when the first liquid crystal alignment solidification layer 21 functions as a λ / 2 plate and the second liquid crystal alignment solidification layer 22 functions as a λ / 4 plate, the thickness of the first liquid crystal alignment solidification layer 21 is, for example, 2.0 μm to 3.0 μm, and the thickness of the second liquid crystal alignment solidification layer 22 is, for example, 1.0 μm to 2.0 μm. In this case, the in-plane phase difference Re(550) of the first liquid crystal alignment solidification layer is preferably 200 nm to 300 nm, more preferably 230 nm to 290 nm, and even more preferably 250 nm to 280 nm. Regarding the in-plane phase difference Re(550) of the second liquid crystal alignment solidification layer, for a single layer, it is as described above. The angle between the slow axis of the first liquid crystal alignment solidification layer and the absorption axis of the polarizer is preferably 10° to 20°, more preferably 12° to 18°, and even more preferably about 15°. The angle between the slow axis of the second liquid crystal alignment solidification layer and the absorption axis of the polarizer is preferably 70° to 80°, more preferably 72° to 78°, and even more preferably about 75°. With this configuration, characteristics approaching ideal anomalous dispersion wavelength characteristics can be obtained, resulting in very excellent anti-reflection properties. Regarding the liquid crystal compounds constituting the first liquid crystal alignment solidification layer and the second liquid crystal alignment solidification layer, the formation method of the first liquid crystal alignment solidification layer and the second liquid crystal alignment solidification layer, optical properties, etc., for the case of a single layer, the above description applies.
[0092] D. Iodine Osmosis Inhibition Layer
[0093] As described above, the iodine permeation suppression layer is a solidified or thermosetting coating of an organic solvent solution of resin. With this configuration, the thickness can be very thin (e.g., less than 10 μm). The thickness of the iodine permeation suppression layer is preferably 0.05 μm to 10 μm, more preferably 0.08 μm to 5 μm, even more preferably 0.1 μm to 1 μm, and particularly preferably 0.2 μm to 0.7 μm. Furthermore, with this configuration, the iodine permeation suppression layer can be formed directly (i.e., without via an adhesive layer or bonding agent) onto adjacent layers (e.g., polarizers, retardation layers). According to embodiments of the present invention, as described above, the polarizer, retardation layer, and iodine permeation suppression layer are very thin, and the adhesive layer or bonding agent layer used for laminating the iodine permeation suppression layer can be omitted, thus enabling an extremely thin total thickness of the polarizing plate with the retardation layer. Furthermore, this iodine permeation suppression layer has the following advantages: compared to solidified aqueous coatings such as aqueous solutions or dispersions, it has lower hygroscopicity and moisture permeability, resulting in excellent humidification durability. Consequently, it is possible to achieve a polarizing plate with a phase retardation layer that maintains its optical properties even under high temperature and high humidity environments and exhibits excellent durability. In addition, compared to cured UV-curable resins, this iodine permeation suppression layer can suppress adverse effects on the polarizing plate (polarizing element) caused by UV irradiation. The iodine permeation suppression layer is preferably a solidified coating of an organic solvent solution of resin. Compared to cured resins, the solidified layer exhibits less shrinkage during film formation and contains no residual monomers, thus suppressing the degradation of the film itself and inhibiting adverse effects on the polarizing plate (polarizing element) caused by residual monomers.
[0094] Furthermore, the resin constituting the iodine penetration suppression layer has a glass transition temperature (Tg) of 85°C or higher and a weight-average molecular weight (Mw) of 25,000 or higher. If the resin's Tg and Mw are within this range, the synergistic effect with the effect of forming an iodine penetration suppression layer from a solidified or thermosetting film of the resin's organic solvent solution can significantly suppress the migration of iodine from the polarizer to the image display unit, even when very thin. As a result, when a polarizer with a phase retardation layer is applied to an image display device, corrosion of metal components can be significantly suppressed. The resin's Tg is preferably 90°C or higher, more preferably 100°C or higher, further preferably 110°C or higher, and particularly preferably 120°C or higher. The upper limit of Tg can be, for example, 200°C. Furthermore, the resin's Mw is preferably 30,000 or higher, more preferably 35,000 or higher, and further preferably 40,000 or higher. The upper limit of Mw can be, for example, 150,000.
[0095] Furthermore, as described above, the iodine permeation suppression layer adjacent to the phase retardation layer in the iodine permeation suppression layer disposed on the polarizer with the phase retardation layer further comprises an isocyanate compound in addition to the aforementioned resin. Examples of isocyanate compounds include toluene diisocyanate, diphenylmethane diisocyanate, phenylenediamine diisocyanate, and their derivatives (e.g., modified compounds, adducts). The isocyanate compound can be used alone or in combination. The content ratio of resin to isocyanate compound (resin / isocyanate compound) is, as described above, 95 / 5 to 10 / 90. The content ratio (resin / isocyanate compound) can be, for example, 95 / 5 to 50 / 50, or more specifically, 90 / 10 to 60 / 40, or more specifically, 85 / 15 to 70 / 30, or more specifically, 85 / 15 to 75 / 25. The resin / isocyanate compound ratio can be, for example, 40 / 60 to 5 / 95, 30 / 70 to 5 / 95, or 20 / 80 to 10 / 90. With this configuration, as described above, the peeling of the iodine penetration inhibition layer and the phase difference layer can be significantly suppressed while maintaining the excellent effect of metal corrosion inhibition.
[0096] As the resin constituting the iodine permeation inhibition layer, any suitable thermoplastic or thermosetting resin can be used, as long as it is a solidified or thermosetting material capable of forming a coating film of an organic solvent solution and has the Tg and Mw as described above. Thermoplastic resins are preferred. Examples of thermoplastic resins include epoxy resins and acrylic resins. Epoxy resins and acrylic resins can be used in combination. Hereinafter, representative examples of epoxy resins and acrylic resins that can be used in the iodine permeation inhibition layer will be described.
[0097] <Epoxy Resin>
[0098] As the epoxy resin, an epoxy resin having aromatic rings is preferred. By using an epoxy resin having aromatic rings, the adhesion between the iodine penetration suppression layer and the polarizer can be improved when the iodine penetration suppression layer is disposed adjacent to the polarizer. Furthermore, when an adhesive layer is disposed adjacent to the iodine penetration suppression layer, the anchoring force of the adhesive layer can be improved. Examples of epoxy resins having aromatic rings include: bisphenol type epoxy resins such as bisphenol A type epoxy resin, bisphenol F type epoxy resin, and bisphenol S type epoxy resin; phenolic varnish type epoxy resins such as phenolic varnish epoxy resin, cresol phenolic varnish epoxy resin, and hydroxybenzaldehyde phenolic varnish epoxy resin; multifunctional epoxy resins such as glycidyl ether of tetrahydroxyphenylmethane, glycidyl ether of tetrahydroxybenzophenone, and epoxidized polyvinylphenol; naphthol type epoxy resin; naphthyl type epoxy resin; and biphenyl type epoxy resin. Bisphenol A type epoxy resin, biphenyl type epoxy resin, and bisphenol F type epoxy resin are preferred. Only one type of epoxy resin can be used, or two or more types can be used in combination.
[0099] <Acrylic Resins>
[0100] Acrylic resins are typically characterized by repeating units derived from (meth)acrylate monomers having a linear or branched structure as their main component. In this specification, (meth)acrylate refers to acrylic acid and / or methacrylic acid. Acrylic resins may contain repeating units derived from any suitable comonomer for the intended purpose. Examples of comonomers include, for instance, carboxyl-containing monomers, hydroxyl-containing monomers, amide-containing monomers, (meth)acrylates containing aromatic rings, and vinyl monomers containing heterocyclic rings. By appropriately setting the type, quantity, combination, and copolymerization ratio of the monomer units, acrylic resins with the aforementioned specified Tg and Mw can be obtained.
[0101] <Boron-containing acrylic resins>
[0102] In one embodiment, the acrylic resin comprises a copolymer (hereinafter sometimes referred to as a boron-containing acrylic resin) obtained by polymerizing a monomer mixture comprising more than 50 parts by weight of a (meth)acrylic monomer and more than 0 parts by weight and less than 50 parts by weight of a monomer of formula (1) (hereinafter sometimes referred to as a comonomer).
[0103]
[0104] (In the formula, X represents a functional group containing at least one reactive group selected from the group consisting of vinyl, (meth)acryloyl, styrene, (meth)acrylamido, vinyl ether, epoxy, oxetyl, hydroxyl, amino, aldehyde, and carboxyl groups; R) 1 and R 2 Each can independently represent a hydrogen atom, an aliphatic hydrocarbon group with optional substituents, an aryl group with optional substituents, or a heterocyclic group with optional substituents, R 1 and R 2 (Optional interconnections form a loop).
[0105] Boron-containing acrylic resins are typically characterized by repeating units as shown in the following formula. By polymerizing a monomer mixture comprising a comonomer and a (meth)acrylic monomer as shown in formula (1), the boron-containing acrylic resin has boron-containing substituents (e.g., repeating units of k in the following formula) on its side chains. This improves the adhesion to the polarizer when the iodine permeation suppression layer is disposed adjacent to it. The boron-containing substituents can be continuously (i.e., in a block form) or randomly contained in the boron-containing acrylic resin.
[0106]
[0107] (where R is in the formula) 6Let j represent any functional group, and k represent integers greater than or equal to 1.
[0108] <(meth)acrylic acid monomers>
[0109] As (meth)acrylic monomers, any suitable (meth)acrylic monomer can be used. Examples include (meth)acrylic ester monomers having a straight-chain or branched structure, and (meth)acrylic ester monomers having a cyclic structure.
[0110] Examples of (meth)acrylate monomers having a straight-chain or branched structure include: methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, methyl 2-ethylhexyl (meth)acrylate, and 2-hydroxyethyl (meth)acrylate. Methyl (meth)acrylate is preferred. Only one (meth)acrylate monomer may be used, or two or more may be used in combination.
[0111] Examples of cyclic monomers of (meth)acrylate include: cyclohexyl (meth)acrylate, benzyl (meth)acrylate, isobornyl (meth)acrylate, 1-adamantyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenoxyethyl (meth)acrylate, dicyclopentenoxyethyl (meth)acrylate, biphenyl (meth)acrylate, o-biphenoxyethyl (meth)acrylate, o-biphenoxyethoxyethyl (meth)acrylate, m-biphenoxyethyl (meth)acrylate, and p-biphenoxyethyl (meth)acrylate. Monomers containing biphenyl groups include methyl ethyl acrylate, o-biphenyloxy-2-hydroxypropyl acrylate, p-biphenyloxy-2-hydroxypropyl acrylate, m-biphenyloxy-2-hydroxypropyl acrylate, N-(meth)acryloyloxyethyl-o-biphenyl=carbamate, N-(meth)acryloyloxyethyl-p-biphenyl=carbamate, N-(meth)acryloyloxyethyl-m-biphenyl=carbamate, o-phenylphenol glycidyl ether acrylate, terphenyl acrylate, and o-triphenoxyethyl acrylate. Preferably, 1-adamantyl acrylate and dicyclopentyl acrylate are used. Using these monomers yields polymers with high glass transition temperatures. Only one monomer may be used, or two or more may be used in combination.
[0112] Furthermore, silsesquioxane compounds having (meth)acryloyl groups can be used instead of the aforementioned (meth)acrylate monomers. By using silsesquioxane compounds, acrylic polymers with high glass transition temperatures can be obtained. Silsesquioxane compounds are known to have various skeletal structures, such as cage-like, ladder-like, and random structures. Silsesquioxane compounds may have only one of these structures or two or more. Silsesquioxane compounds may use only one type or a combination of two or more types.
[0113] As silsesquioxane compounds containing (meth)acryloyl groups, examples include the MAC and AC grades from the SQ series manufactured by Toa Synthetic Industries, Ltd. MAC grade compounds are silsesquioxane compounds containing methacryloyl groups, such as MAC-SQ TM-100, MAC-SQ SI-20, and MAC-SQ HDM. AC grade compounds are silsesquioxane compounds containing acryloyl groups, such as AC-SQ TA-100 and AC-SQ SI-20.
[0114] (Meth)acrylic monomers are used in amounts exceeding 50 parts by weight per 100 parts by weight of the monomer mixture.
[0115] <Comonomer>
[0116] The monomer shown in formula (1) above can be used as the comonomer. By using this comonomer, boron-containing substituents are introduced into the side chains of the resulting polymer. Only one comonomer can be used, or two or more can be used in combination.
[0117] Examples of aliphatic hydrocarbon groups in formula (1) above include: alkyl groups with 1 to 20 carbon atoms that are either straight-chain or branched, cyclic alkyl groups with 3 to 20 carbon atoms that are either substituted, and alkenyl groups with 2 to 20 carbon atoms. Examples of aryl groups above include: phenyl groups with 6 to 20 carbon atoms that are either substituted, and naphthyl groups with 10 to 20 carbon atoms that are either substituted. Examples of heterocyclic groups include: 5-membered or 6-membered cyclic groups containing at least one heteroatom that are either substituted. It should be noted that R 1 and R 2 They can be arbitrarily connected to form a loop. R 1 and R 2 Preferably, it is a hydrogen atom or a straight-chain or branched alkyl group having 1 to 3 carbon atoms, more preferably a hydrogen atom.
[0118] The reactive group represented by X, containing a functional group, is selected from at least one group chosen from the group consisting of vinyl, (meth)acryloyl, styrene, (meth)acrylamido, vinyl ether, epoxy, oxetyl, hydroxyl, amino, aldehyde, and carboxyl. Preferably, the reactive group is (meth)acryloyl and / or (meth)acrylamido. By having these reactive groups, the adhesion to the polarizer can be further improved when the iodine penetration suppression layer is disposed adjacent to the polarizer.
[0119] In one embodiment, the functional group represented by X is preferably the functional group represented by ZY. Here, Z represents a functional group comprising at least one reactive group selected from the group consisting of vinyl, (meth)acryloyl, styryl, (meth)acrylamido, vinyl ether, epoxy, oxetyl, hydroxyl, amino, aldehyde, and carboxyl, and Y represents phenylene or alkylene.
[0120] The following compounds can be used as comonomers.
[0121]
[0122] The comonomer is used in an amount of more than 0 parts by weight and less than 50 parts by weight relative to 100 parts by weight of the monomer mixture. Preferably, it is 0.01 parts by weight or more and less than 50 parts by weight, more preferably 0.05 parts by weight to 20 parts by weight, even more preferably 0.1 parts by weight to 10 parts by weight, and particularly preferably 0.5 parts by weight to 5 parts by weight.
[0123] <Acrylic resins containing lactone rings, etc.>
[0124] In another embodiment, the acrylic resin has repeating units comprising a ring structure selected from lactone ring units, glutaric anhydride units, glutarimide units, maleic anhydride units, and maleimide (N-substituted maleimide) units. The repeating units comprising the ring structure may include only one type or more types in the repeating units of the acrylic resin.
[0125] The lactone ring unit is preferably as shown in the following general formula (2).
[0126]
[0127] In general formula (2), R 2 R 3 and R 4 Each of these units independently represents a hydrogen atom or an organic residue with 1 to 20 carbon atoms. It should be noted that the organic residue may contain an oxygen atom. Acrylic resins may contain only a single lactone ring unit, or they may contain R from the general formula (2) above. 2 R 3 and R4 Different multiple lactone ring units. Acrylic resins having lactone ring units are described, for example, in Japanese Patent Application Publication No. 2008-181078, the contents of which are incorporated herein by reference.
[0128] The glutarimide unit is preferably as shown in the following general formula (3).
[0129]
[0130] In general formula (3), R 11 and R 12 Each independently represents hydrogen or an alkyl group having 1 to 8 carbon atoms, R 13 It represents an alkyl group having 1 to 18 carbon atoms, a cycloalkyl group having 3 to 12 carbon atoms, or an aryl group having 6 to 10 carbon atoms. In general formula (3), R is preferred. 11 and R 12 Each independently is either hydrogen or methyl, R 13 It is hydrogen, methyl, butyl, or cyclohexyl. More preferably, R 11 Methyl, R 12 For hydrogen, R 13 It is methyl. Acrylic resins may contain only a single glutarimide unit, or they may contain R from the general formula (3) above. 11 R 12 and R 13 Different multiple glutarimide units. Acrylic resins having glutarimide units are described, for example, in Japanese Patent Application Publication Nos. 2006-309033, 2006-317560, 2006-328334, 2006-337491, 2006-337492, 2006-337493, and 2006-337569, the contents of which are incorporated herein by reference. It should be noted that, regarding the glutaric anhydride unit, in addition to the R in the above general formula (3), 13 The above description relating to the glutarimide unit can be applied when the substituted nitrogen atom is not an oxygen atom.
[0131] Regarding the maleic anhydride unit and the maleimide (N-substituted maleimide) unit, their structures can be determined from their names, so detailed descriptions are omitted.
[0132] The acrylic resin contains repeating units with ring structures at a ratio preferably of 1 mol% to 50 mol%, more preferably 10 mol% to 40 mol%, and even more preferably 20 mol% to 30 mol%. It should be noted that the acrylic resin contains repeating units derived from the above-mentioned (meth)acrylic monomers as the main repeating units.
[0133] The iodine penetration inhibition layer can be formed by coating a resin solution of the above-described organic solvent to form a coating film, and then solidifying or thermally curing the coating film. As the organic solvent, any suitable organic solvent capable of dissolving or uniformly dispersing acrylic resins can be used. Specific examples of organic solvents include: ethyl acetate, toluene, methyl ethyl ketone (MEK), methyl isobutyl ketone (MIBK), cyclopentanone, and cyclohexanone. The resin concentration of the solution relative to 100 parts by weight of the solvent is preferably 3 to 20 parts by weight. With this resin concentration, a uniform coating film can be formed.
[0134] The solution can be applied to any suitable substrate or to an adjacent layer (e.g., a polarizer or retardation layer). When the solution is applied to the substrate, the solidified form of the coating film (iodine penetration inhibition layer) formed on the substrate is transferred to the adjacent layer. When the solution is applied to the adjacent layer, a protective layer is formed directly on the adjacent layer by drying (solidifying) the coating film. Preferably, the solution is applied to the adjacent layer, and the protective layer is formed directly on the adjacent layer. With this configuration, the adhesive or bonding agent layer required for transfer can be omitted, thus allowing for a thinner polarizer with a retardation layer. Any suitable method can be used for applying the solution. Specific examples include: roller coating, spin coating, lead bar coating, dip coating, die coating, curtain coating, spray coating, and doctor blade coating (comma coating, etc.).
[0135] An iodine penetration-inhibiting layer can be formed by solidifying or thermally curing the coating film of the solution. The heating temperature for solidification or thermal curing is preferably below 100°C, more preferably 50°C to 70°C. If the heating temperature is within this range, adverse effects on the polarizing element can be prevented. The heating time can vary depending on the heating temperature. For example, the heating time can be from 1 minute to 10 minutes.
[0136] The iodine penetration-inhibiting layer (essentially an organic solvent solution of the aforementioned resin) may contain any appropriate additives depending on the purpose. Specific examples of additives include: ultraviolet absorbers; leveling agents; hindered antioxidants such as phenols, phosphorus compounds, and sulfur compounds; stabilizers such as light stabilizers, weather stabilizers, and heat stabilizers; reinforcing materials such as glass fiber and carbon fiber; near-infrared absorbers; flame retardants such as tris(dibromopropyl) phosphate, triallyl phosphate, and antimony oxide; antistatic agents such as anionic, cationic, and nonionic surfactants; colorants such as inorganic pigments, organic pigments, and dyes; organic or inorganic fillers; resin modifiers; organic and inorganic fillers; plasticizers; lubricants; antistatic agents; flame retardants; and so on. The type, quantity, combination, and dosage of additives can be appropriately determined according to the purpose.
[0137] E. Other phase difference layers
[0138] As described above, the other phase retardation layer can be a so-called positive C-plate whose refractive index characteristics show a relationship of nz > nx = ny. By using a positive C-plate as the other phase retardation layer, oblique reflection can be effectively prevented, and a wide field of view with anti-reflection function can be achieved. In this case, the phase difference Rth(550) in the thickness direction of the other phase retardation layer is preferably -50nm to -300nm, more preferably -70nm to -250nm, even more preferably -90nm to -200nm, and particularly preferably -100nm to -180nm. Here, "nx = ny" includes not only the case where nx and ny are strictly equal, but also the case where nx and ny are substantially equal. That is, the in-plane phase difference Re(550) of the other phase retardation layer can be less than 10nm.
[0139] Other retardation layers having refractive index characteristics of nz>nx=ny can be formed from any suitable material. These other retardation layers are preferably formed from a thin film containing a liquid crystal material fixed in a vertical orientation. The liquid crystal material (liquid crystal compound) capable of vertical orientation can be a liquid crystal monomer or a liquid crystal polymer. As specific examples of the liquid crystal compound and the method for forming the retardation layer, the liquid crystal compound and the method for forming the retardation layer described in Japanese Patent Application Publication Nos. 2002-333642
[0020] to
[0028] can be cited. In this case, the thickness of the other retardation layer is preferably 0.5 μm to 10 μm, more preferably 0.5 μm to 8 μm, and even more preferably 0.5 μm to 5 μm.
[0140] F. Conductive layer or isotropic substrate with conductive layer
[0141] The conductive layer can be formed on any suitable substrate by depositing a metal oxide film using any appropriate film-forming method (e.g., vacuum evaporation, sputtering, CVD, ion plating, spraying, etc.). Examples of metal oxides include indium oxide, tin oxide, zinc oxide, indium-tin composite oxide, tin-antimony composite oxide, zinc-aluminum composite oxide, and indium-zinc composite oxide. Among these, indium-tin composite oxide (ITO) is preferred.
[0142] When the conductive layer comprises a metal oxide, the thickness of the conductive layer is preferably 50 nm or less, more preferably 35 nm or less. The lower limit of the thickness of the conductive layer is preferably 10 nm.
[0143] The conductive layer can be transferred from the aforementioned substrate to the retardation layer (or other retardation layers in the presence of an iodine penetration suppression layer or the like), and the conductive layer can serve as a constituent layer of a polarizing plate with a retardation layer on its own, or it can be laminated onto the retardation layer (or other retardation layers in the presence of an iodine penetration suppression layer or the like) as a laminate with the substrate (the substrate with the conductive layer). Preferably, the aforementioned substrate is optically isotropic; therefore, the conductive layer can be used as an isotropic substrate with a conductive layer in a polarizing plate with a retardation layer.
[0144] As an optically isotropic substrate (isotropic substrate), any suitable isotropic substrate can be used. Examples of materials constituting the isotropic substrate include: materials with a main backbone of resins without a conjugated system, such as norbornene resins and olefin resins; and materials with cyclic structures such as lactone rings and glutarimide rings in the main chain of acrylic resins. Using such materials allows for smaller control over the expression of phase difference along with molecular chain orientation when forming the isotropic substrate. The thickness of the isotropic substrate is preferably 50 μm or less, more preferably 35 μm or less. The lower limit of the thickness of the isotropic substrate is, for example, 20 μm.
[0145] The conductive layer described above and / or the conductive layer of the isotropic substrate with the conductive layer described above can be patterned as needed. Through patterning, conductive and insulating portions can be formed. As a result, electrodes can be formed. The electrodes can function as touch sensor electrodes for sensing contact with the touchscreen. Any suitable method can be used as a patterning method. Specific examples of patterning methods include wet etching and screen printing.
[0146] G. Image display device
[0147] The polarizing plate with a phase retardation layer described in items A through F above can be applied to image display devices. Therefore, embodiments of the present invention include image display devices using such a polarizing plate with a phase retardation layer. Representative examples of image display devices include liquid crystal display devices and electroluminescent (EL) display devices (e.g., organic EL display devices, inorganic EL display devices). The image display device of the embodiments of the present invention has a polarizing plate with a phase retardation layer described in items A through F above on its recognition side. The polarizing plate with the phase retardation layer is stacked such that the phase retardation layer is located on the image display unit (e.g., liquid crystal unit, organic EL unit, inorganic EL unit) side (the polarizing element is located on the recognition side). This image display device significantly suppresses corrosion of metal components while being very thin. In one embodiment, the image display device has a curved shape (essentially a curved display screen), and / or can be bent or folded.
[0148] Example
[0149] The present invention will now be specifically described through examples, but the present invention is not limited to these examples. The methods for measuring each characteristic are as follows. It should be noted that, unless otherwise specified, "parts" and "%" in the examples and comparative examples are based on weight.
[0150] (1) Thickness
[0151] Thicknesses below 10 μm were measured using an interferometric film thickness gauge (manufactured by Otsuka Electronics Co., Ltd., product name "MCPD-3000"). Thicknesses exceeding 10 μm were measured using an electronic micrometer (manufactured by Anritsu Corporation, product name "KC-351C").
[0152] (2) Metal Corrosion 1
[0153] On one side of a 50 μm polyethylene terephthalate (PET) film, a silver nanowire liquid (manufactured by Merck, nanowire size: diameter 115 nm, length 20 μm–50 μm, solid content 0.5% isopropanol (IPA) solution) was coated with a wire-wound bar to a wet film thickness of 15 μm. The coated film was then dried in an oven at 100°C for 5 minutes to form a silver nanowire coating. Next, an external coating liquid (solid content concentration: approximately 1%) containing 99 parts methyl isobutyl ketone (MIBK), 1 part pentaerythritol tetraacrylate (PETA), and 0.03 parts photopolymerization initiator (manufactured by BASF, product name "IRGACURE 907") was coated with a wire-wound bar to a wet film thickness of 10 μm. This was then dried in an oven at 100°C for 5 minutes. Next, the outer coating was cured by irradiation with active energy rays, creating a metal film with a structure of PET film / silver nanowire layer / outer coating (100 nm thick). This metal film was then bonded to a 0.5 mm thick glass plate using an adhesive (15 μm) to obtain a metal film / adhesive / glass plate laminate. The resistance of the resulting laminate was measured using a non-contact resistance meter (manufactured by Napson Corporation, product name "EC-80"), and the result was 50 Ω / □.
[0154] The polarizing plate with a phase retardation layer obtained in the examples and comparative examples was bonded to the outer coating surface of the metal film of the laminate, serving as a test sample. The resistance value of this test sample was measured using a non-contact resistance meter and recorded as the initial resistance value. Then, the test sample was subjected to a reliability test (placed at 85°C and 85% RH for 48 hours, and then at 23°C and 55% RH for 2 hours), and the resistance value was measured in the same manner as above. The rate of increase in resistance value was calculated using the following formula. It should be noted that if the measured value (resistance value) exceeds the measurement limit (1000 Ω / □) of the non-contact resistance meter, the measured value is assumed to be 1500 Ω / □.
[0155] Resistance increase rate (%) = {(Resistance value after reliability test - Initial resistance value) / Initial resistance value} × 100
[0156] Therefore, the evaluation will be conducted according to the following criteria.
[0157] ○: Resistance increase rate is less than 200%
[0158] ×: Resistance increase rate is over 200%
[0159] (3) Metal corrosivity 2
[0160] Similar to "(2) Metal Corrosion 1", a polarizing plate with a phase retardation layer obtained in the Examples and Comparative Examples was bonded to the outer coating surface of the metal film of the laminate as a test sample. The resistance value of the test sample was measured using a non-contact resistance meter and recorded as the initial resistance value. The test sample was subjected to a reliability test (placed at 85°C and 85% RH for 200 hours, and then placed at 23°C and 55% RH for 2 hours). The following steps were performed in the same manner as in "(2) Metal Corrosion 1", and the rate of increase in resistance value was calculated and evaluated according to the following criteria.
[0161] ○: Resistance increase rate is less than 200%
[0162] △: The rate of increase in resistance is greater than 200% but less than 2000%.
[0163] ×: Resistance increase rate is over 2000%
[0164] (4) Peel test
[0165] A 50mm x 50mm section of the polarizing plate with a phase retardation layer obtained in the examples and comparative examples was cut and bonded to a glass plate larger than the cut size to serve as a test sample. This test sample was immersed in a constant temperature bath at 20°C and 98% RH for 240 hours. After removing the test sample from the constant temperature bath, a 3mm incision was made at a corner of the polarizing plate with the phase retardation layer using a Phillips screwdriver. Adhesive tape (manufactured by Nichiban Co., Ltd., 18mm wide) was applied to the incision, and the polarizing plate with the phase retardation layer was peeled off from the glass at high speed. The process of applying and peeling the adhesive tape twice at one corner was performed to confirm the interlayer delamination of the polarizing plate with the phase retardation layer. Cases where no delamination occurred at any of the four corners were rated as "○", and cases where delamination occurred at even one corner were rated as "×".
[0166] [Manufacturing Example 1: Production of Boron-Containing Acrylic Resin]
[0167] 99.0 parts by weight of methyl methacrylate (MMA, manufactured by FUJIFILM Wako Pure Chemical Corporation, trade name: methyl methacrylate monomer), 1.0 part by weight of monomer of general formula (1e), and 0.2 parts by weight of polymerization initiator (manufactured by FUJIFILM Wako Pure Chemical Corporation, trade name: 2,2'-azobis(isobutyronitrile)) were dissolved in 100 parts by weight of toluene. Then, a polymerization reaction was carried out for 5 hours under a nitrogen atmosphere at 70°C to obtain copolymer 1 (solids concentration: 50% by weight). Copolymer 1 has a Tg of 110°C and a weight-average molecular weight of 80,000.
[0168] [Manufacturing Example 2: Fabrication of a Polarizing Plate]
[0169] 1. Fabrication of polarizing components
[0170] As the thermoplastic resin substrate, a strip-shaped, amorphous polyethylene terephthalate (PET) copolymer film with a water absorption rate of 0.75%, a Tg of approximately 75°C, and a thickness of 100 μm was used. One side of the resin substrate was subjected to corona treatment.
[0171] Add 13 parts by weight of potassium iodide to 100 parts by weight of a PVA resin obtained by mixing polyvinyl alcohol (degree of polymerization 4200, degree of saponification 99.2 mol%) and acetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., trade name "GOHSEFIMER Z410") in a ratio of 9:1, dissolve the mixture in water, and prepare a PVA aqueous solution (coating solution).
[0172] The above-mentioned PVA aqueous solution is coated on the corona-treated surface of the resin substrate and dried at 60°C, thereby forming a PVA resin layer with a thickness of 13μm, and a laminate is made.
[0173] The resulting laminate was subjected to unidirectional stretching at the free end to 2.4 times its original length (air-assisted stretching treatment) between rollers with different circumferential speeds in an oven at 130°C.
[0174] Next, the laminate was immersed in an insoluble bath (an aqueous solution of boric acid prepared by mixing 4 parts by weight of boric acid relative to 100 parts by weight of water) at a liquid temperature of 40°C for 30 seconds (insoluble treatment).
[0175] Next, the polarizer is immersed in a dyeing bath (an iodine aqueous solution prepared by mixing iodine and potassium iodide in a weight ratio of 1:7 relative to 100 parts by weight of water) at a liquid temperature of 30°C for 60 seconds (dyeing treatment) while adjusting the concentration so that the monomer transmittance (Ts) of the final polarizer is 43.0% or higher.
[0176] Next, it is immersed in a crosslinking bath at a liquid temperature of 40°C (an aqueous solution of boric acid prepared by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid relative to 100 parts by weight of water) for 30 seconds (crosslinking treatment).
[0177] Then, while immersing the laminate in a boric acid aqueous solution (boric acid concentration 4.0 wt% and potassium iodide concentration 5 wt%) at a liquid temperature of 70°C, it is subjected to unidirectional stretching (water stretching treatment) in the longitudinal direction (length direction) between rollers with different circumferential speeds at a total stretch ratio of 5.5 times.
[0178] Then, the laminate is immersed in a cleaning bath at a liquid temperature of 20°C (an aqueous solution of 4 parts by weight of potassium iodide mixed with 100 parts by weight of water) (cleaning treatment).
[0179] Then, while drying in an oven maintained at 90°C, it is brought into contact with SUS heated rollers with a surface temperature maintained at 75°C for approximately 2 seconds (drying shrinkage treatment). The width-direction shrinkage of the laminate resulting from the drying shrinkage treatment is 5.2%.
[0180] In this way, a polarizing element with a thickness of 5μm is formed on the resin substrate.
[0181] 2. Fabrication of polarizing plates
[0182] An HC-COP film is bonded as a protective layer to the surface of the obtained polarizer (the side opposite to the resin substrate) using a UV-curable adhesive. Specifically, the adhesive is coated with a total thickness of 1.0 μm and bonded using a rolling mill. Then, UV light is irradiated from the protective layer side to cure the adhesive. It should be noted that the HC-COP film is a film with a 2 μm thick hard coating (HC) layer formed on a cycloolefin (COP) film (manufactured by ZEON CORPORATION, product name "ZF12", thickness 25 μm), and the COP film is bonded with the polarizer side facing down. Next, the resin substrate is peeled off to obtain a polarizing plate with a structure of protective layer (HC layer / COP film) / adhesive layer / polarizer.
[0183] [Manufacturing Example 3: Fabrication of the first and second orientation solidification layers constituting the phasing layer]
[0184] A liquid crystal composition (coating solution) was prepared by dissolving 10 g of a polymerizable liquid crystal (manufactured by BASF: trade name "Paliocolor LC242", as shown below) exhibiting a nematic liquid crystal phase and 3 g of a photopolymerization initiator for the polymerizable liquid crystal compound (manufactured by BASF: trade name "IRGACURE 907") in 40 g of toluene.
[0185]
[0186] An orientation treatment was performed by rubbing the surface of a 38 μm thick polyethylene terephthalate (PET) film with a rubbing cloth. The orientation direction was 15° relative to the absorption axis of the polarizer when viewed from the identification side when bonded to the polarizer. The aforementioned liquid crystal coating solution was then applied to the orientation-treated surface using a bar coater and dried at 90°C for 2 minutes, thereby orienting the liquid crystal compound. The liquid crystal layer thus formed was irradiated with a metal halide lamp at 1 mJ / cm². 2 The light is used to solidify the liquid crystal layer, thereby forming a liquid crystal alignment solidification layer A on the PET film. The thickness of the liquid crystal alignment solidification layer A is 2.5 μm, and the in-plane phase difference Re(550) is 270 nm. Furthermore, the liquid crystal alignment solidification layer A has a refractive index distribution of nx > ny = nz.
[0187] The coating thickness was changed, and the alignment direction was set to 75° relative to the absorption axis of the polarizer when viewed from the identification side. Otherwise, the process was the same as described above, forming a liquid crystal alignment solidification layer B on the PET film. The thickness of the liquid crystal alignment solidification layer B was 1.5 μm, and the in-plane phase difference Re(550) was 140 nm. Furthermore, the liquid crystal alignment solidification layer B had a refractive index distribution of nx > ny = nz.
[0188] [Example 1]
[0189] The surface of the polarizer obtained in Manufacturing Example 2 is sequentially transferred with the liquid crystal alignment solidification layer A and the liquid crystal alignment solidification layer B obtained in Manufacturing Example 3. The transfer (bonding) is performed with an angle of 15° between the absorption axis of the polarizer and the slow axis of the liquid crystal alignment solidification layer A, and an angle of 75° between the absorption axis of the polarizer and the slow axis of the liquid crystal alignment solidification layer B. It should be noted that the transfer (bonding) is performed using the UV-curable adhesive (1.0 μm thick) used in Manufacturing Example 2. Thus, a laminate with a structure of protective layer (HC layer / COP film) / adhesive layer / polarizer / adhesive layer / phase retardation layer (first liquid crystal alignment solidification layer / adhesive layer / second liquid crystal alignment solidification layer) is manufactured.
[0190] 95 parts of a blend of copolymer 1 (boron-containing acrylic resin) (converted to solid content) and thermoplastic epoxy resin (manufactured by Mitsubishi Chemical Corporation, trade name "jER (registered trademark) YX6954BH30") obtained in Manufacturing Example 1, and 5 parts of isocyanate compound (manufactured by Tosoh Corporation, "CORONATE L": trimethylolpropane adduct of toluene diisocyanate). The resin blend had a Tg of 125°C and a weight-average molecular weight of 46,000. The blend was dissolved in 80 parts of a mixed solvent of ethyl acetate / cyclopentanone (70 / 30) to obtain a resin solution (20%). The resin solution was coated onto the surface of the second liquid crystal alignment solidification layer of the above-obtained laminate using a wire rod, and the coated film was dried at 60°C for 5 minutes to form an iodine penetration inhibition layer (thickness 0.5 μm) consisting of a solidified coating film of the resin organic solvent solution. Next, an adhesive layer (15 μm thick) was deposited on the surface of the iodine permeation suppression layer to obtain a polarizing plate with a phase retardation layer having a structure of protective layer (HC layer / COP film) / adhesive layer / polarizing element / adhesive layer / phase retardation layer (first liquid crystal alignment solidification layer / adhesive layer / second liquid crystal alignment solidification layer) / iodine permeation suppression layer / adhesive layer. The total thickness of the obtained polarizing plate with phase retardation layer was 39.5 μm. The obtained polarizing plate with phase retardation layer was subjected to the evaluation described in (2) to (4) above. The results are shown in Table 1.
[0191] [Example 2]
[0192] An iodine permeation inhibition layer was formed using a mixture containing 90 parts isocyanate compound relative to 10 parts of the resin blend. Otherwise, the process was the same as in Example 1 to fabricate a polarizing plate with a phase retardation layer. The resulting polarizing plate with the phase retardation layer was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0193] [Example 3]
[0194] An iodine permeation suppression layer was formed using a mixture containing 20 parts of isocyanate compound relative to 80 parts of resin blend. This iodine permeation suppression layer was also formed between the polarizer and the first liquid crystal alignment solidification layer. Otherwise, the process was the same as in Example 1, producing a polarizing plate with a phase retardation layer structure consisting of a protective layer (HC layer / COP film) / adhesive layer / polarizer / adhesive layer / iodine permeation suppression layer / phase retardation layer (first liquid crystal alignment solidification layer / adhesive layer / second liquid crystal alignment solidification layer) / adhesive layer. The resulting polarizing plate with the phase retardation layer was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0195] [Example 4]
[0196] An iodine penetration inhibition layer was formed using a mixture containing 20 parts of isocyanate compound relative to 80 parts of copolymer 1 (boron-containing acrylic resin), otherwise the same procedure as in Example 1 was followed to fabricate a polarizing plate with a phase retardation layer. The resulting polarizing plate with a phase retardation layer was subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0197] [Example 5]
[0198] An iodine penetration inhibition layer was formed using a mixture of 80 parts of thermoplastic epoxy resin (manufactured by Mitsubishi Chemical Corporation, trade name "jER (registered trademark) YX6954BH30") and 20 parts of isocyanate compound. Otherwise, the process was the same as in Example 1 to prepare a polarizing plate with a phase retardation layer. The epoxy resin had a Tg of 130°C and a weight-average molecular weight of 38,000. The resulting polarizing plate with the phase retardation layer was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0199] [Example 6]
[0200] As a thermoplastic epoxy resin, "jER (registered trademark) YX7200B35" manufactured by Mitsubishi Chemical Corporation was used instead of "YX6954BH30" to form the iodine penetration inhibition layer. Otherwise, the process was the same as in Example 5 to produce a polarizing plate with a phase retardation layer. The epoxy resin had a Tg of 150°C and a weight-average molecular weight of 30,000. The resulting polarizing plate with the phase retardation layer was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0201] [Example 7]
[0202] An iodine permeation suppression layer was formed using a mixture containing 20 parts of an isocyanate compound (manufactured by Tosoh Corporation, "CORONATE 2067": a trimethylolpropane adduct of diphenylmethane diisocyanate) relative to 80 parts of the resin blend. Otherwise, the process was the same as in Example 1, and a polarizing plate with a phase retardation layer was fabricated. The resulting polarizing plate with the phase retardation layer was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0203] [Example 8]
[0204] An iodine permeation suppression layer was formed using a mixture containing 20 parts of an isocyanate compound (manufactured by Mitsui Chemicals, Ltd., "TAKENATE D110N": a trimethylolpropane adduct of isophthalamide diisocyanate) relative to 80 parts of the resin blend. Otherwise, the process was the same as in Example 1, and a polarizing plate with a phase retardation layer was fabricated. The resulting polarizing plate with the phase retardation layer was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0205] [Example 9]
[0206] An iodine permeation suppression layer, using only copolymer 1 (i.e., without isocyanate compounds), was further formed between the polarizer and the first liquid crystal alignment solidification layer. Otherwise, the process was the same as in Example 3, producing a polarizer with a phase retardation layer having a structure of a protective layer (HC layer / COP film) / adhesive layer / polarizer / iodine permeation suppression layer / adhesive layer / phase retardation layer (first liquid crystal alignment solidification layer / adhesive layer / second liquid crystal alignment solidification layer) / iodine permeation suppression layer / adhesive layer. The resulting polarizer with a phase retardation layer was evaluated in the same way as in Example 1. The results are shown in Table 1.
[0207] [Example 10]
[0208] An iodine permeation suppression layer, identical to that in Example 3, was further formed between the polarizer and the first liquid crystal alignment solidification layer. Otherwise, the process was the same as in Example 3, to fabricate a polarizer with a phase retardation layer having a structure of protective layer (HC layer / COP film) / adhesive layer / polarizer / adhesive layer / iodine permeation suppression layer / phase retardation layer (first liquid crystal alignment solidification layer / adhesive layer / second liquid crystal alignment solidification layer) / iodine permeation suppression layer / adhesive layer. The resulting polarizer with a phase retardation layer was subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0209] [Example 11]
[0210] Between the polarizer and the first liquid crystal alignment solidification layer, an iodine permeation suppression layer using only copolymer 1 (i.e., without isocyanate compounds) and the same iodine permeation suppression layer as in Example 3 are further formed sequentially from the polarizer side. Otherwise, the process is the same as in Example 3, producing a polarizing plate with a phase retardation layer having a structure of protective layer (HC layer / COP film) / adhesive layer / polarizer / iodine permeation suppression layer / adhesive layer / iodine permeation suppression layer / phase retardation layer (first liquid crystal alignment solidification layer / adhesive layer / second liquid crystal alignment solidification layer) / iodine permeation suppression layer / adhesive layer. The resulting polarizing plate with a phase retardation layer is evaluated in the same way as in Example 1. The results are shown in Table 1.
[0211] [Comparative Example 1]
[0212] No iodine penetration inhibition layer was formed. Otherwise, the process was the same as in Example 1, producing a polarizing plate with a phase retardation layer having a structure of a protective layer (HC layer / COP film) / adhesive layer / polarizer / adhesive layer / phase retardation layer (first liquid crystal alignment solidification layer / adhesive layer / second liquid crystal alignment solidification layer) / adhesive layer. The resulting polarizing plate with the phase retardation layer was evaluated in the same way as in Example 1. The results are shown in Table 1.
[0213] [Comparative Example 2]
[0214] An iodine permeation suppression layer was formed using only acrylic resin (Kushumoto Chemical Co., Ltd. "B-723", Tg: 54°C, Mw: 200,000) (i.e., without isocyanate compounds). Otherwise, the process was the same as in Example 1, and a polarizing plate with a phase retardation layer was fabricated. The resulting polarizing plate with the phase retardation layer was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0215] [Comparative Example 3]
[0216] An iodine permeation suppression layer was formed using only a resin blend (i.e., without isocyanate compounds), otherwise the process was the same as in Example 1, to fabricate a polarizing plate with a phase retardation layer. The resulting polarizing plate with the phase retardation layer was subjected to the same evaluation as in Example 1. The results are shown in Table 1.
[0217] [Comparative Example 4]
[0218] An iodine permeation suppression layer was formed using a mixture containing 20 parts of an isocyanate compound (manufactured by Mitsui Chemicals, Ltd., "TAKENATE D160N": a trimethylolpropane adduct of hexamethylene diisocyanate) relative to 80 parts of the resin blend. Otherwise, the process was the same as in Example 1, and a polarizing plate with a phase retardation layer was fabricated. The resulting polarizing plate with the phase retardation layer was evaluated in the same manner as in Example 1. The results are shown in Table 1.
[0219] [Table 1]
[0220]
[0221] It should be noted that in Table 1, "epoxy / acrylic" in the "resin composition" column indicates a blend of epoxy and acrylic resins; the numbers in the "formation location" column are reference numerals. Therefore, for example, "11" indicates a polarizing element.
[0222] [evaluate]
[0223] As shown in Table 1, the polarizing plate with a phase retardation layer in the embodiments of the present invention can significantly suppress metal corrosion under high temperature and high humidity environments. Therefore, it can be seen that the polarizing plate with a phase retardation layer in the embodiments of the present invention can suppress corrosion of metal components when applied to image display devices. Furthermore, comparing Embodiments 1-8 with Embodiments 9-11 shows that by providing two or more iodine penetration suppression layers, metal corrosion can be significantly suppressed. In addition, the polarizing plate with a phase retardation layer in the embodiments of the present invention also suppresses the peeling of the iodine penetration suppression layer from the phase retardation layer.
[0224] Industrial availability
[0225] The polarizing plate with phase décor layer of the present invention can be suitably used as a circular polarizing plate for liquid crystal display devices, organic EL display devices and inorganic EL display devices.
[0226] Explanation of reference numerals in the attached figures
[0227] 10 polarizing plates
[0228] 11 polarizers
[0229] 12 protective layers
[0230] 20 phase difference layers
[0231] 30 adhesive layers
[0232] 40 Iodine Osmosis Inhibition Layer
[0233] 100 polarizing plates with phase retardation layers
[0234] 101 Polarizing plate with phase retardation layer
[0235] 102 Polarizing plate with phase retardation layer
[0236] 103 Polarizing plate with phase retardation layer
[0237] 104 polarizing plate with phase retardation layer
[0238] 105 Polarizing plate with phase retardation layer
[0239] 106 polarizing plates with phase retardation layers
[0240] 107 Polarizing plate with phase retardation layer
[0241] 108 polarizing plates with phase retardation layers
[0242] 109 Polarizing plate with phase retardation layer
Claims
1. A polarizing plate with a phase difference layer, The optical device has, in order from the identification side: a polarizing plate including a polarizer, a phase difference layer, and an adhesive layer. At least one iodine permeation inhibiting layer is provided between the polarizer and the adhesive layer, wherein the iodine permeation inhibiting layer is a solidified product or a thermally cured product of a coating film of an organic solvent solution of a resin. The iodine permeation suppression layer adjacent to the phase difference layer contains a resin and an isocyanate compound. The resin has a glass transition temperature of 85° C. or higher and a weight average molecular weight Mw of 25,000 or higher. The isocyanate compound is at least one selected from toluene diisocyanate, diphenylmethane diisocyanate, xylylene diisocyanate and derivatives thereof, The content ratio of the resin to the isocyanate compound, that is, resin / isocyanate compound, is 95 / 5 to 10 / 90. 2 . The polarizing plate with a retardation layer according to claim 1 , comprising two or more iodine permeation suppressing layers.
3. The polarizing plate with a phase difference layer according to claim 2, wherein: At least one of the two or more iodine-permeation suppressing layers is provided adjacent to the retardation layer.
4. The polarizing plate with a phase difference layer according to claim 2, wherein: One of the two or more iodine-permeation suppressing layers is provided adjacent to the polarizer.
5. The polarizing plate with a retardation layer according to any one of claims 1 to 4, wherein The thickness of the iodine permeation inhibition layer is 0.05 μm to 10 μm.
6. The polarizing plate with a retardation layer according to any one of claims 1 to 4, wherein The resin constituting the iodine permeation suppressing layer includes an epoxy resin.
7. The polarizing plate with a retardation layer according to any one of claims 1 to 4, wherein The resin constituting the iodine permeation inhibiting layer comprises a copolymer obtained by polymerizing a monomer mixture comprising more than 50 parts by weight of a (meth)acrylic monomer and more than 0 parts by weight and less than 50 parts by weight of a monomer represented by formula (1), In formula (1), X represents a functional group containing at least one reactive group selected from the group consisting of a vinyl group, a (meth)acryloyl group, a styryl group, a (meth)acrylamide group, a vinyl ether group, an epoxy group, an oxetane group, a hydroxyl group, an amino group, an aldehyde group, and a carboxyl group, and R 1 and R 2 Each independently represents a hydrogen atom, an aliphatic hydrocarbon group which may have a substituent, an aryl group which may have a substituent, or a heterocyclic group which may have a substituent, and R 1 and R 2 Optionally, they are linked to each other to form a ring.
8. The polarizing plate with a retardation layer according to any one of claims 1 to 4, wherein The phase difference layer is an alignment solidified layer of a liquid crystal compound having a circular polarization function or an elliptically polarization function.
9. The polarizing plate with a phase difference layer according to any one of claims 1 to 4, wherein: The phase difference layer is a single layer, The Re (550) of the phase difference layer is 100nm to 190nm. The angle formed between the slow axis of the phase difference layer and the absorption axis of the polarizer is 40° to 50°.
10. The polarizing plate with a retardation layer according to any one of claims 1 to 4, wherein The phase difference layer has a stacked structure of an alignment solidification layer of a first liquid crystal compound and an alignment solidification layer of a second liquid crystal compound. The Re (550) of the alignment solidification layer of the first liquid crystal compound is 200 nm to 300 nm, and the angle between the slow axis and the absorption axis of the polarizer is 10° to 20°. The Re (550) of the alignment solidification layer of the second liquid crystal compound is 100 nm to 190 nm, and the angle formed between the slow axis and the absorption axis of the polarizer is 70° to 80°. 11 . The polarizing plate with a retardation layer according to claim 1 , which has a total thickness of 60 μm or less. 12 . An image display device comprising the polarizing plate with a retardation layer according to claim 1 . 13 . The image display device according to claim 12 , which is an organic electroluminescent display device or an inorganic electroluminescent display device.
Citation Information
Patent Citations
Liq. crystalline (LC) material
DE19504224A1
Novel polymerizable liquid crystalline compounds
DE4408171A1
Liquid crystalline reticulated polysiloxanes
EP0066137A1
Picture display cell, method of forming an orientation layer on a substrate of the picture display cell and monomeric compounds for use in the orientation layer
EP0261712A1
Liquid crystal polyorganosiloxanes containing (meth)acryloxy groups
EP0358208A2